Assemblage Structure of the Ichthyoplankton and Its Relationship With Environmental Factors in Spring and Autumn off the Pearl River Estuary - Hou, Gang; Wang, Jinrun; Liu, Limei; Chen, Yanying; Pan, Chuanhao; Lin, Jianbin; Zhang, Hui (Frontiers in Marine Science, 2021)
Ichthyoplankton assemblages and their relationship with environmental variables are investigated in waters off the Pearl River Estuary in spring and autumn of 2019. Of 80 ichthyoplankton taxa identified using DNA barcode and morphological methods, 61 are identified to species. The most abundance families (Carangidae, Trichiuridae, Mullidae, and Scombridae) account for 61.34% of the horizontal total catch in spring, while Menidae and Carangidae are the most abundant families identified in autumn, accounting for 89.72% of the horizontal total catch. Cluster analysis identifies three species assemblages in spring, and four in autumn based on horizontal trawls. Relationships between assemblage structure and environmental variables (in situ and remote sensed) are determined by canonical correspondence analysis. Ichthyoplankton assemblage structure appears to be strongly influenced by sea level anomalies, salinity, water depth, temperature at 10 m depth, and distance from shore. We demonstrate the efficacy of using DNA barcode to identify ichthyoplankton, and suggest how these data can be used to protect fish spawning grounds in waters off the Pearl River Estuary.